2014
DOI: 10.1039/c4lc00485j
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo biolasing of fluorescent proteins suspended in liquid microdroplet cavities

Abstract: Fluorescent proteins are indispensable for selective, quantitative visualization of localization, dynamics, and interactions of key molecular constituents of live cells. Incorporation of fluorescent proteins into an optical cavity can lead to a significant increase in fluorescence signal levels due to stimulated emission and light amplification in the cavity, forming a laser with biological gain medium. Utilization of lasing emission from fluorescent biological molecules can then greatly enhance the performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(60 citation statements)
references
References 30 publications
1
58
0
1
Order By: Relevance
“…No cell damage has been observed at the pump energy levels used throughout most of this study (less than 100 nJ). This agrees with the previous studies, which showed cell damage above approximately 1 µJ [8,12].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…No cell damage has been observed at the pump energy levels used throughout most of this study (less than 100 nJ). This agrees with the previous studies, which showed cell damage above approximately 1 µJ [8,12].…”
Section: Discussionsupporting
confidence: 83%
“…An even more recently formed strand of research aspires to generate laser light from biomaterials in situ in live cells. Exploiting the fact that GFP and other fluorescent proteins can be produced by a wide variety of live organisms, live cells have been incorporated into cavities to enable lasing: For instance, GFP expressing E. coli bacteria were used as biological gain medium in Fabry-Perot [11] and microdroplet cavities [12], and we have shown the first biological lasers based on single human cell expressing GFP [8] or cells containing fluorescent dyes [13], using a Fabry-Perot type cavity. We have also demonstrated microcavity lasers inside cells in the form of fluorescent solid beads [14][15][16] or droplets, including naturally occurring lipid droplets inside adipocyte cells [14].…”
Section: Introductionmentioning
confidence: 99%
“…Scale bar is 5µm. Reproduced from [60] with permission from The Royal Society of Chemistry. Image of an array of microdroplets in a microfluidic cavity capable of acting as a distributed feedback mirror.…”
Section: Discussionmentioning
confidence: 99%
“…This results in a large number of droplets with which to carry out experiments, but effectively means that each laser droplet is a single shot device. Other methods for making droplets include coagulation on a wire [59], resulting in droplets in the 100s of micrometer range and nebulizers [60] which produce droplets typically in the sub-ten-micrometre diameter range when designed for medical applications.…”
Section: Experimental Considerationsmentioning
confidence: 99%
See 1 more Smart Citation